Pengaruh Bauran Pemasaran 7p Terhadap Keputusan Penggunaan Jasa Pada Poplens Self Photo Studio - Mandalena Heni Setyowati; andi hasrun; Masseni (At-Thariqah: Jurnal Ekonomi, 2025)
This study aims to determine the influence of marketing strategies on service usage decisions at Poplens Self Photo Studio. This study used a quantitative approach with a sample of 94 respondents who used Poplens Self Photo Studio services. Data were collected through distributed questionnaires and analyzed using SPSS 26 using multiple linear regression analysis, t-tests, and F-tests. The results showed that partially, the variables Product, Price, and Place had a significant positive effect on service usage decisions. Meanwhile, the variables Promotion and Physical Evidence were found to have a significant negative effect. The variables People and Process did not show a significant effect. Simultaneously, all marketing mix variables (7Ps) were proven to have a positive and significant effect on service usage decisions, with an F-value of 23.568>2.12 and a significance level of 0.000<0.05, and were able to explain 62.9% of the service usage decision variable. These results confirm that an integrated marketing mix plays a crucial role in shaping customer decisions at Poplens Self Photo Studio.